One pearl from the precious string. Series 3, Issue 5. - Hassan @ Mohamed, Nor Jana (Centre for Islamisation (CENTRIS), IIUM, 2025)
We greet you with Salām, spreading peace in this turbulent era. Islamisation-Herald resumes its No. 3 series with Issue 5, October 2025 | Rabi‘ al-Akhir 1447, with further details of the ‘HOW’ of IOHK, as laid down by Emeritus Professor Tan Sri Dr. Mohd Kamal Hassan, Allāh yarḥamuhu. IOHK is to develop the integrated personality types of Ūlū al-Albāb – the God-fearing ‘Ulamā’ (scholars) and the true believers who are committed to the civilisational vision and mission of Islam; who project the peaceful and compassionate image of Raḥmatan li’l-‘Ālamῑn, and portray the ethical and humane behaviour of true Khulafā’ and servants of Allah.